THE TYPES AND THE FUNCTIONS OF THE FILLERS USED IN BARACK OBAMAS SPEECHES - Paulus Yanuar Kharismawan (International Journal of Humanity Studies (IJHS), 2017)
This study deals with the production of fillers used in Barack Obamas speeches. This study is to investigate the types and functions of fillers used by Barack Obama. The study seeks to answer two research questions: (1) what are the types of fillers in Barack Obamas speeches? and (2) What are the functions of fillers in Barack Obamas speeches? In order to answer these problems, the researcher applied Roses (1998) theory on the types of fillers which combined with similar notions on the types and functions of fillers which taken from Stenstr (1994) and Baalen (2001). This study adopted a descriptive qualitative approach which used a discourse analysis to conduct this study. This study aims to introduce the types and the functions of fillers and to increase the learners awareness of fillers when they hesitate in the foreign language, which is actually the very nature of speaking.